Carnot battery technology: A state-of-the-art review. (December 2020) - Dumont, Olivier; Frate, Guido Francesco; Pillai, Aditya; Lecompte, Steven; De paepe, Michel; Lemort, Vincent
Highlights: There is a need for large scale electrical energy storage. The Carnot battery allows to store electricity at low cost with no geographical constraints. Each configuration of Carnot battery is described. A comparison is proposed including a state of the art, potential on the energy market and existing prototypes. Abstract: The growth of renewable energy requires flexible, low-cost and efficient electrical storage to balance the mismatch between energy supply and demand. The Carnot battery buffers electrical energy by storing thermal energy (charging cycle mode) from a resistive heater or a heat pump system when the electricity production is higher than the demand. When electricity demand is higher than the production, the Carnot battery generates power from the stored thermal energy (power cycle mode). This paper is a review of this emerging and innovative technology, including a market analysis. First, the different possible technologies and configurations of Carnot batteries are described. This includes charging cycles, power cycles and thermal energy storage systems. Furthermore, a state-of-the-art of the existing prototypes in the world is given. The performance indicators for this technology are unclear, and this paper tries to define objective performance indicators. Finally, all the described technologies are compared, and conclusions are drawn to help engineers select the optimal technology for a given case.